Textual and Contextual Hadith Analysis: Study of Asbabul Wurud in The Content of The @Rahmadotid Instagram Account - Bowode, Fadhilah; Taufiq, Muhammad; Pramana, Yogi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Background and Objectives : Social media has become a new space for conveying understandings of hadith, including through the Instagram account @rahmadotid, which actively discusses religious issues related to women. This study aims to examine how the reading of asbāb al-wurūd is applied in the hadith content uploaded by the account. Methodology: This research uses qualitative methods and library research. The focus of this research is the @rahmadotid Instagram account because it is a social media that actively answers religious issues, especially related to women. This research is limited to three hadith contents, namely the hadith about the prohibition of wives rejecting their husbands' invitations, the hadith about dowry, and the hadith about the wife's deeds that lead to heaven. Main Results: The research shows that the Instagram account @rahmadotid understands the first hadith contextually by reading the macro asbab al-wurud. The second hadith is understood contextually through the connection with other narrations without including asbab al-wurud. While the third tradition is understood textually because no asbab al-wurud is found related to the tradition. From these three traditions, it appears that the @rahmadotid Instagram account seeks to present an understanding that is just for women. Contribution:This study contributes by mapping the contextual and textual approaches used in the interpretation of hadith on social media. The findings highlight efforts to present hadith interpretations that are more just and equitable for women in digital spaces. Conclusion:The results of the study show that the reading of asbāb al-wurūd is applied variably according to the characteristics of each hadith examined. This approach produces interpretations that are more inclusive and responsive to issues concerning women.